COMORBID CARDIORESPIRATORY PATHOLOGY AND BEHAVIORAL RISK FACTORS: A NEW LOOK AT OLD PROBLEM - T. N. Vasilkova; Yu. A. Rybina (Бюллетень сибирской медицины)
The material for the study included patients with chronic obstructive pulmonary disease (COPD) in association with arterial hypertension (AH) II stage – 50 people. A comprehensive clinical and functional study of the assessment of emotional status. Found that with the increase of the severity of COPD and hypertension increases the frequency and severity of cognitive impairment up to dementia.